A DFT study on an alkali atom doped decahedral silver nanocluster for potential application in opto-electronics and catalysis. Issue 10 (6th February 2015) - Debnath, Shaikat; Mohd Said, Suhana; Roslan, Muhammad Faris; Mohd Sabri, Mohd Faizul; Long, Bui Duc
<x xml:space="preserve">Abstract</x> Electronic and optical properties of silver–alkali metals alloys are explored and lithium doped silver nanoclusters are found to have excellent potential for opto-electronics and catalysis.